Impact of government’s motorcycle subsidy on job performance of agriculture extension officers in Southern province in Sri Lanka - Manathunga, M.M.C.S.; Sliva, K.N.N.; Weerasinghe, T.W.M.K.K. (University of Jaffna, 2021)
Agricultural Extension is an ongoing, non-formal educational process that takes place over a period of time to transfer knowledge to rural farmers. In Sri Lanka, the ratio of farmers to extension officers is 800:1, and therefore, one extension officer has to extensively work with a larger group of farmers with a limited resource capacity. Considering these facts, the Sri Lankan government decided to provide motorcycle subsidy under National Budget Circular 2/2014 to increase the job performance and well-being of the Agricultural Inspectors. Even though the foresaid objective of this subsidy scheme is to improve the performances, there were no follow-up monitoring and evaluation system for this scheme. Therefore, this research is aimed at evaluating the impact of the government’s motorcycle subsidy on job performance and well-being of Agricultural Inspectors in the southern province of Sri Lanka. The sample of 48 Agricultural Inspectors was randomly selected from 70 Agricultural Inspectors in the Galle district. Descriptive and inferential statistics tests were mainly used to analyze the data. Among the general constraints faced by the Agricultural Inspectors, the distance to be traveled, a higher number of farmers and area to be covered per day and less infrastructural facilities were major constraints. Importantly, the study revealed that the motorcycle subsidy has significantly affected the job performance of the Agricultural Inspectors directly by facilitating to perform their job roles and saving more time for Agricultural Inspectors to enhance their personal and career development through knowledge acquisitions.
Keywords: Agricultural inspectors; Job performance; Motorcycle subsidy; Well-being